2002
DOI: 10.1046/j.1525-1438.2002.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinicopathologic factors in malignant mixed Mullerian tumors of the uterine corpus

Abstract: The aim of this study was to retrospectively analyze the clinical and pathologic data of a series of patients presenting to our unit with uterine malignant mixed Müllerian tumors (MMMT) to attempt to identify prognostic factors and relate them to survival. Thirty-seven patients diagnosed with MMMT of the uterus from 1988 through 2000 were identified from the gynecological tumor registry. Data was abstracted and analyzed. The effect of a variety of clinical, histopathologic, and surgical variables on recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 22 publications
(52 reference statements)
1
27
1
11
Order By: Relevance
“…Unlike what was reported in the review by Kanthan and Senger [1] , in which nulliparity was identified as a risk factor for the development of this tumour, most of our patients were uni-or multiparous (75%). In agreement with the current literature, there was a frequent association with chronic diseases, mainly with hypertension and diabetes [15,20] . In 13.6% of the cases there was an association with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike what was reported in the review by Kanthan and Senger [1] , in which nulliparity was identified as a risk factor for the development of this tumour, most of our patients were uni-or multiparous (75%). In agreement with the current literature, there was a frequent association with chronic diseases, mainly with hypertension and diabetes [15,20] . In 13.6% of the cases there was an association with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In 13.6% of the cases there was an association with breast cancer. Over half of the women included in our study had a good performance status, which represents another divergence from the typical patient profile described in many reports [20] . The presenting symptom of this neoplasm often was abnormal uterine bleeding in post-menopause (40.9%) [15] , even if the patients frequently were asymptomatic (54.5%) [21] .…”
Section: Discussioncontrasting
confidence: 58%
“…Other factors that have been associated with prognosis include patient age, LVSI, and presence of gross residual disease [22]. …”
Section: Surveillance and Prognosismentioning
confidence: 99%
“…2 The third common variant is carcinosarcoma, which is composed of mixture of sarcoma and carcinoma. 3 Almost all of the carcinosarcomas occur after menopause, at a median age of 62 years. It is considered to be highly malignant as the disease extends outside the uterus in 40 to 60 % of cases at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%